Sistem Penjualan Makanan Khas Aceh Berbasis Web di Toko Ridha Kue Lampisang Kabupaten Aceh Besar - Mawardinur (Yayasan Kawanad, 2024)
Traditional Acehnese cuisine preservation requires innovative digital approaches to reach broader markets beyond local communities. This research develops a web-based sales system for Ridha Kue Lampisang Store to address current operational limitations and expand market accessibility. The store currently operates through traditional methods, serving customers only at their physical location in Lampisang, Aceh Besar, with manual transaction recording systems. Key challenges include the absence of online marketing capabilities and geographic limitations restricting customer access. This study employs a system development methodology using PHP, MySQL, JavaScript, HTML5, and CSS3 technologies to create a comprehensive e-commerce platform. The research follows a structured approach including system analysis, design, implementation, and testing phases. The developed web-based system successfully addresses operational challenges by providing 24/7 accessibility, automated transaction processing, and digital inventory management. Performance testing demonstrates excellent results with 1.2-second response time, 0.2% error rate, and 4.4/5.0 user satisfaction rating. The system achieves significant operational improvements including 60% efficiency increase, 60% faster transaction processing, and 95% inventory accuracy. Financial analysis reveals a remarkable 145% return on investment, with annual benefits of Rp 110.4 million against Rp 45 million investment. The platform successfully eliminates geographical barriers, enabling customers to purchase traditional Acehnese cakes anytime and anywhere. This digital transformation not only preserves cultural heritage but also enhances business sustainability and economic prosperity for traditional food vendors.